7st+4t(t+s+4)-9t=

Simple and best practice solution for 7st+4t(t+s+4)-9t= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7st+4t(t+s+4)-9t= equation:


Simplifying
7st + 4t(t + s + 4) + -9t = 0

Reorder the terms:
7st + 4t(4 + s + t) + -9t = 0
7st + (4 * 4t + s * 4t + t * 4t) + -9t = 0

Reorder the terms:
7st + (4st + 16t + 4t2) + -9t = 0
7st + (4st + 16t + 4t2) + -9t = 0

Reorder the terms:
7st + 4st + 16t + -9t + 4t2 = 0

Combine like terms: 7st + 4st = 11st
11st + 16t + -9t + 4t2 = 0

Combine like terms: 16t + -9t = 7t
11st + 7t + 4t2 = 0

Solving
11st + 7t + 4t2 = 0

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-7t' to each side of the equation.
11st + 7t + -7t + 4t2 = 0 + -7t

Combine like terms: 7t + -7t = 0
11st + 0 + 4t2 = 0 + -7t
11st + 4t2 = 0 + -7t
Remove the zero:
11st + 4t2 = -7t

Add '-4t2' to each side of the equation.
11st + 4t2 + -4t2 = -7t + -4t2

Combine like terms: 4t2 + -4t2 = 0
11st + 0 = -7t + -4t2
11st = -7t + -4t2

Divide each side by '11t'.
s = -0.6363636364 + -0.3636363636t

Simplifying
s = -0.6363636364 + -0.3636363636t

See similar equations:

| 2.50+1.5(m-1)=17.50 | | 110d=115d+45 | | 4/6=x/11 | | 13r-39=10r | | 6x+5x-x= | | 65+k=8 | | 9x-5-14=17 | | (x-2)2=49xiswhat | | y=x^2-6x+9forx | | y=x^2-6y+9 | | 14lnx=17 | | 585=X^2 | | x+17+8=25 | | 3x(2x+40)=180 | | 5y^2+10y-120=0 | | 6(2x+y)= | | -3/2=2x^2 | | 2(x+5)=90 | | -3=1/2x-4 | | 2s^2-s-10=0 | | 1/4k=3(-1/4k+3) | | 1x-6=9 | | (.1x-33)+(.4x-40)=180 | | x=2x-132 | | (-3x+79)= | | 7st+4t(t+s+4)-9= | | x+7-4=-15 | | 300=-(420*600*1500)-(-1c*600*1500)-(1000*600*1500) | | -14+3x=11 | | 3u-8=-20 | | -10y=x+21 | | 4y-5+y+19=5y+20-2y |

Equations solver categories